Intelligence, security, and vehicular sensor networks in internet of things (IoT)-enabled smart-cities: An overview. (October 2020) - Al-Turjman, Fadi; Lemayian, Joel Poncha
Abstract: Security in Vehicular Sensor Networks (VSNs) is a critical subject that must be addressed in the emerging Intelligent Transport Systems (ITS). Users share confidential information that can be used against them by attackers. Popular attacks include Malwares and Spams, Black Holes, Wormholes, and Physical/Electronic Outages. Such VSN attacks can lead to loss of life due to road accidents and breach of privacy. In this paper, we overview the VSN concept in a vehicular IoT-based smart city paradigm, focusing on the security aspects. In addition, we discuss the design features of VSN, its robustness, and reliability. We also discuss relevant communication technologies and their security concerns. We highlight the main open research issues in literature and provide hints for overcoming them. This analysis concludes that VSNs play a key role in developing efficient ITS. Nevertheless, current VSNs security standards must be improved for a reliable, and safe transportation system.